2018
DOI: 10.3382/ps/pex303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of emulsifier blends having different hydrophilic-lipophilic balance value on growth performance, nutrient digestibility, serum lipid profiles, and meat quality of broilers

Abstract: Energy is a major cost component in diets for poultry. We hypothesized that the supplementation of emulsifier blends in broiler diets may contribute to the efficient utilization of energy and in increasing fat digestibility, thereby improving performance. To test our hypothesis, an experiment was conducted to evaluate the effect of a blend of emulsifiers on growth performance, nutrient digestibility, serum lipid profiles, and meat quality of broilers. A total of 768 1-d-old Ross 308 male broiler chicks with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
58
7
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 20 publications
14
58
7
3
Order By: Relevance
“…Our results are in agreement with those reported by Arnouts and Lippens (2006) who observed a tendency of decreased FCR in the grower-finisher periods but no significant effect in the starter period, when 0.05% Globin was added to the feed. Other studies have found a lower FCR and a higher fat digestibility during grower and finisher periods when other emulsifiers were used in broiler diets (Kaczmarek et al 2015;Upadhaya et al 2018). In contrast to the present study, Arnouts and Lippens (2006), Kaczmarek et al (2015) and Upadhaya et al (2018) did not find any effects on performance or digestibility during the starter period.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results are in agreement with those reported by Arnouts and Lippens (2006) who observed a tendency of decreased FCR in the grower-finisher periods but no significant effect in the starter period, when 0.05% Globin was added to the feed. Other studies have found a lower FCR and a higher fat digestibility during grower and finisher periods when other emulsifiers were used in broiler diets (Kaczmarek et al 2015;Upadhaya et al 2018). In contrast to the present study, Arnouts and Lippens (2006), Kaczmarek et al (2015) and Upadhaya et al (2018) did not find any effects on performance or digestibility during the starter period.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have found a lower FCR and a higher fat digestibility during grower and finisher periods when other emulsifiers were used in broiler diets (Kaczmarek et al 2015;Upadhaya et al 2018). In contrast to the present study, Arnouts and Lippens (2006), Kaczmarek et al (2015) and Upadhaya et al (2018) did not find any effects on performance or digestibility during the starter period. The differences in effects on performance and fat digestibility as a result of dietary emulsifiers could be related to the dietary content of the saturated and unsaturated FAs, the sex of the birds and/or the type and dosage of the emulsifier.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, limited research conducted with the exogenous emulsifiers and inconsistent results were noted with broiler studies. A couple of studies observed improved growth performance and nutrient digestibility of the broiler chickens [6,7]. Contrary, Cho et al [8] and Zampiga et al [9] reported emulsifier had no such effect on growth performance in broiler chickens.…”
Section: Introductionmentioning
confidence: 97%